Space-Surface Bistatic SAR Image Formation Algorithms - Antoniou, M.; Cherniakov, M.; Cheng Hu (IEEE transactions on geoscience and remote sensing, 2009)
This paper presents algorithms designed for a subclass of bistatic synthetic aperture radar (BSAR) called space-surface BSAR (SS-BSAR). Two SS-BSAR configurations are considered. The first one assumes a stationary, spaceborne transmitter and a moving airborne receiver. The second case is the generalized SS-BSAR configuration, where the transmitter is nonstationary. The transmitter and receiver have essentially different flight paths and velocities. For each configuration under investigation, the characteristics of the corresponding SS-BSAR received signal are examined first. Then, each proposed algorithm is derived analytically, and verified via simulation.